MEDIA PEMBELAJARAN PAI BERBASIS INFORMASI KOMUNIKASI DAN TEKNOLOGI BAGI ANAK DISABILITAS DISEKOLAH KHUSUS KORPRI - Jihan Handi Suryadi; M. Noor Anzali; Agus Hidayatullah; Basirun Basirun (STIT Al-Marhalah Al-Ulya Bekasi, 2023)
ABSTRACTThe development and progress of the times always have implications for the development of technology, communication and information that are adapted to human needs and demands. The technologies developed by the technocrats also vary, in the form of biotechnology, multimedia technology and communication technology which have made a significant contribution to education. So, with this technology it is hoped that this development can also improve the quality of Indonesia's inclusive education in the future as a strategic component of human development (human resources) and development of the country.This study aims to determine the implementation and responsibility of students related to Information, Communication and Technology-Based PAI Learning Media for Children with Disabilities in Korpri Special Schools.The results of the study show that the implementation of information, communication and technology-based PAI learning media for children with disabilities is very good. Due to the background of the majority of teachers and education and full dedication to children with special needs. In this case, of course, the achievements made by students are good because the response is also very good. Interest, curiosity, good response, and having potential skills are certainly highly expected by teachers. Many say that children with disabilities are children who are not perfect, but after I enjoyed the essence of this research, it turns out that a perfect child is not just a child who has strengths, but a child who has both strengths and weaknesses.Keywords: PAI Learning Media, Information Communication and Technology, disability